2021
DOI: 10.1200/go.21.00001
|View full text |Cite
|
Sign up to set email alerts
|

Locally Advanced Breast Cancer (LABC): Real-World Outcome of Patients From Cancer Institute, Chennai

Abstract: PURPOSE There are sparse data on the outcome of patients with locally advanced breast cancer (LABC). This report is on the prognostic factors and long-term outcome from Cancer Institute, Chennai. METHODS This is an analysis of untreated patients with LABC (stages IIIA-C) who were treated from January 2006 to December 2013. RESULTS Of the 4,577 patients with breast cancer who were treated, 2,137 patients (47%) with LABC were included for analysis. The median follow-up was 75 months (range, 1-170 months), and 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
1
9
0
2
Order By: Relevance
“…Our study suggested that the survival in LABC patients was not consistently unsatisfactory, with a 5 year OS of ~40–75% as described in previous studies ( 2 , 3 ). CS was a novel survival assessment method that allowed real-time estimation of changes in survival based on survived time ( 9 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study suggested that the survival in LABC patients was not consistently unsatisfactory, with a 5 year OS of ~40–75% as described in previous studies ( 2 , 3 ). CS was a novel survival assessment method that allowed real-time estimation of changes in survival based on survived time ( 9 ).…”
Section: Discussionsupporting
confidence: 83%
“…Locally advanced breast cancer (LABC) is a relatively advanced stage of breast cancer, but benefitting from advances in diagnosis and treatment strategies, the overall survival (OS) has improved in recent years (1)(2)(3). Therefore, more and more long-term survivors hoped to know more accurate prognostic information during follow-up, but LABC still lacked effective prognostic assessment tools.…”
Section: Introductionmentioning
confidence: 99%
“…Locally advanced breast cancer (LABC) is rare and represents about 5% of newly diagnosed breast cancers; in some less affluent countries however, LABC is present in a higher proportion of patients [ 37 ]. There is no universally agreed on definition of LABC.…”
mentioning
confidence: 99%
“…Проведенный в ходе нашего исследования факторный анализ показал, что предикторы, оказывающие существенное влияние на разные типы выживаемости, отличаются. В мировой литературе нам не удалось найти масштабных исследований, посвященных данному вопросу, однако есть ряд работ, описывающих значение лишь отдельных факторов [10][11][12][13][14][15][16][17][18].…”
Section: обсуждение обсуждениеunclassified
“…В мировой литературе указан ряд и других факторов, влияющих на ОВ. Так, в исследовании Dhanushkodi M et al многофакторный анализ показал, что пациенты с размером опухоли более 10 см, тройным негативным подтипом, отсутствием полного патоморфологического ответа и наличием лимфоваскулярной инвазии (р = 0,001) имели достоверно худшую общую выживаемость [10].…”
Section: обсуждение обсуждениеunclassified